2006
DOI: 10.1186/1471-2407-6-67
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms of the XRCC1, XRCC3 and XPDgenes and risk of colorectal adenoma and carcinoma, in a Norwegian cohort: a case control study

Abstract: BackgroundGenetic polymorphisms in DNA repair genes may influence individual variation in DNA repair capacity, which may be associated with risk of developing cancer. For colorectal cancer the importance of mutations in mismatch repair genes has been extensively documented. Less is known about other DNA repair pathways in colorectal carcinogenesis. In this study we have focused on the XRCC1, XRCC3 and XPD genes, involved in base excision repair, homologous recombinational repair and nucleotide excision repair,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
85
6
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(105 citation statements)
references
References 38 publications
13
85
6
1
Order By: Relevance
“…(95% CI=0.96-5.4). Our findings are in concordance with those reported by Mort et al (2003), Krupa et al (2011) andImporta et al (2008) and contradictory to those reported by many authors (Tranah et al, 2004;Stern et al, 2005;Yeh et al, 2005;Skjelbred et al, 2006) which show negative association. Also, it has been suggested that variant genotypes of XRCC3 have decreased repair capacity and thus individuals with this genotypes do not repair double strand DNA breaks efficiently by HRR and are susceptible to risk of CRC (Krupa et al, 2011).…”
Section: Discussioncontrasting
confidence: 56%
“…(95% CI=0.96-5.4). Our findings are in concordance with those reported by Mort et al (2003), Krupa et al (2011) andImporta et al (2008) and contradictory to those reported by many authors (Tranah et al, 2004;Stern et al, 2005;Yeh et al, 2005;Skjelbred et al, 2006) which show negative association. Also, it has been suggested that variant genotypes of XRCC3 have decreased repair capacity and thus individuals with this genotypes do not repair double strand DNA breaks efficiently by HRR and are susceptible to risk of CRC (Krupa et al, 2011).…”
Section: Discussioncontrasting
confidence: 56%
“…For example, the results of the study of Skjelbred CF et al studies on Norwegian cohort suggested that XPD A18911C (Lys751Gln) variant is associated with an increased risk of low-risk adenomas, but not carcinomas [15], while Hansen's RD et al studies on 160,725 Danish individuals revealed that the XPD A18911C (Lys751Gln) variant is not of a major importance in colorectal carcinogenesis [22]. Results similar to those of Hansen et al [22] were recently published by ref.…”
Section: Discussionmentioning
confidence: 99%
“…The 194Trp variant has also been found to be protective against lung cancer, although it is associated with an increased risk of CRC [8]. The results for the Arg399Gln polymorphism of the XRCC1 gene in colorectal cancer epidemiology are very ambiguous [13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…XRCC3 deficient HCT116 cells have shown increased sensitivity to cisplatin and mitomycin C (42). Although some studies have shown no association between polymorphisms in XRCC3 and colorectal cancer risk (43)(44)(45)(46) other studies have (47,48), and in addition XRCC3 polymorphisms have also been associated with breast and lung cancer susceptibility (41,49).…”
Section: Discussionmentioning
confidence: 99%